Przepływy bezpośrednich inwestycji zagranicznych na świecie w latach 1980-2006 - Popławski, Maciej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the article there was shown the process of the foreign direct investments inflow in the world between 1980 and 2006. There were selected stages of the inflow and location of FDI in the world regarding the particular groups of countries and structure of FDI according to the sectors. There was pointed an increasing meaning of multinational corporations in the developing and transition economies, in particular the domination of Asian multinationals. At the end there was shown the influence of FDI in the developing and transition economies development according to theory. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 481-490